2016
DOI: 10.1111/jonm.12382
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between job demand and burnout in nurses: does it depend on work engagement?

Abstract: The prevailing paradigm in combating burnout in nursing can be changed and could be based on the enhancement of nurses' strengths through increasing engagement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 46 publications
3
50
1
1
Order By: Relevance
“…Our finding is also in parallel with the results of prior studies which were conducted among Spanish and Portuguese nurses, respectively (García‐Sierra et al. ; Orgambídez‐Ramos & de Almeida ). However, supports from family and friends were a not significant predictor for work engagement in our study, which may be ascribed to the fact that friends or family members usually lack similar work experiences, which may result in difficulty in work‐related emotional sharing and disclosure and in providing constructive recommendations.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our finding is also in parallel with the results of prior studies which were conducted among Spanish and Portuguese nurses, respectively (García‐Sierra et al. ; Orgambídez‐Ramos & de Almeida ). However, supports from family and friends were a not significant predictor for work engagement in our study, which may be ascribed to the fact that friends or family members usually lack similar work experiences, which may result in difficulty in work‐related emotional sharing and disclosure and in providing constructive recommendations.…”
Section: Discussionsupporting
confidence: 92%
“…It was found that Chinese haemodialysis nurses reported a moderate level of engagement in work, which is lower than those among nurses working in multiple hospital wards, such as the department of internal medicine, surgery, oncology and gerontology in Spain (García‐Sierra et al. ). It is known that compared with other developed countries, China experiences a more severe nursing shortage, and Chinese nurses have heavier workloads and are required to serve a higher percentage of the clients (about 2.4 nurses per 1000 population) (OECD ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To clarify targeted strategies that enhance work engagement, identifying potentially modifiable factors that stimulate work engagement is imperative. Previous studies have shown that reward (Adriaenssens, Gucht, & Maes, ; Wang, Liu, Zou, Hao, & Wu, ), job control (Adriaenssens et al, ; Van Bogaert et al, ), supervisor and/or coworker support (García‐Sierra, Fernández‐Castro, & Martínez‐Zaragoza, ; Poulsen, Khan, Poulsen, Khan, & Poulsen, ), and nurse–physician collaboration (Van Bogaert et al, ) were positively and significantly associated with work engagement. These work‐related factors have been recognized as potential predictors of work engagement among nonpsychiatric nurses.…”
Section: Introductionmentioning
confidence: 99%